Analysis of Contemporary Islamic Thought (Critical Study of Mohammed Arkoun's Thought) - APRILIANA, Milda (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This study examines the thoughts of Mohammed Arkoun in the context of modern Islamic intellectual developments, which offer a critical and rational approach to freeing Muslims from a dogmatic and literal understanding of religious texts.Methodology:Arkoun emphasizes the importance of rationality and deconstruction of traditional thought to open up a more dynamic and contextual interpretation space. He also advocates pluralism and interfaith dialogue as a response to global challenges and proposes a reinterpretation of Islamic history with a more inclusive perspective.Findings:This study divides Arkoun's thoughts into three main aspects: first, a rational and critical approach to understanding Islam contextually in order to remain relevant and contribute to a just and tolerant society; second, deconstruction of traditional Islamic thought by rejecting dogmatic rigidity and integrating science into religious interpretation; third, promotion of pluralism and interfaith dialogue to build a more inclusive Islam, with educational reform as the key to fostering social harmony.Implication:Through his thoughts, Arkoun seeks to help Muslims adapt to modern developments without losing the essence of religious teachings.